REPRESENTASI MENTALITAS JOKOWI: Menyoal Narasi Public Sphere di Balik Kasus “Papa Minta Saham” - Jalaluddin Basyir (Ilmu Komunikasi UIN Alauddin Makassar, 2017)
This study focuses on how the public sphere articulated and played by a state leader(President). In connection with it, it aims to unveil the efforts of the stateleader who articulates and plays the public sphere. The method of this study is focused on the type of qualitative research with a critical analysisof JurgenHabermas’s perspectivewhich concentrateswith the notion of the public sphere as a communicative action that accentuates an analysis of the social reality built by the State. The results of this study explains that the idea of public sphereundergoes a significant change that no longer place people as its main subject, but also get the state involved into the rotation of this public sphere through internalizing the State as a subject that should be heard and protected, not to mention as the object of talk. The implication of this study is to demonstrate that public sphere will be more accommodating to individuals or groups who are good at playing the discursivesof grass root people.